2012
DOI: 10.1089/apc.2011.0409
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence: A Predictor of Worse HIV Outcomes and Engagement in Care

Abstract: For HIV-infected patients, experiencing multiple traumas is associated with AIDS-related and all-cause mortality, increased opportunistic infections, progression to AIDS, and decreased adherence to therapy. The impact of intimate partner violence (IPV) on adherence and HIV outcomes is unknown. HIV-infected patients recruited from a public HIV clinic participated in this observational cohort study (n = 251). Participants completed interviews evaluating IPV and covariates. CD4 count < 200 (CD4 < 200), detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 35 publications
8
108
0
1
Order By: Relevance
“…We wished to determine whether IPV, as a possible social determinant of health in HIV-infected individuals, had a measurable impact on the standard parameters of health used in HIV care. Although we did not find significant cross-sectional differences in viral load or CD4 count, as recently reported in a clinic study [36], progression of HIV disease to an AIDS-defining illness is probably of greater clinical importance. We found that the victims of IPV who presented early enough to avoid most AIDSdefining illnesses with appropriate care (CD4 Ն 200 cells/ mL) were still twice as likely to progress to AIDS, even after adjusting for confounders, when compared with patients who had not experienced IPV.…”
Section: Discussionsupporting
confidence: 53%
“…We wished to determine whether IPV, as a possible social determinant of health in HIV-infected individuals, had a measurable impact on the standard parameters of health used in HIV care. Although we did not find significant cross-sectional differences in viral load or CD4 count, as recently reported in a clinic study [36], progression of HIV disease to an AIDS-defining illness is probably of greater clinical importance. We found that the victims of IPV who presented early enough to avoid most AIDSdefining illnesses with appropriate care (CD4 Ն 200 cells/ mL) were still twice as likely to progress to AIDS, even after adjusting for confounders, when compared with patients who had not experienced IPV.…”
Section: Discussionsupporting
confidence: 53%
“…Previous research has found that intimate partner violence is associated with missed HIV appointments. 82 Financial difficulties were highlighted as one of the key barriers to attendance. Other barriers, including lack of child care and work responsibilities, were often raised and, although the effects of homelessness or immigration issues were less prevalent, they had a clear and direct impact on EIC for some people.…”
Section: Objective 5: Factors Influencing Outpatient Attendancementioning
confidence: 99%
“…[1][2][3] HIV-positive women with childhood abuse histories, including both physical and sexual abuse in childhood, have been identified as a particularly vulnerable population, with higher rates of unprotected sex, greater numbers of partners, and additional health risk behaviors, such as substance use, and poorer adherence than their counterparts without abuse histories. [4][5][6][7][8][9] One potentially relevant mechanism linking abuse and engagement in unprotected sex is disclosure of HIV status. Women with childhood abuse histories report less assertive behavior, greater interpersonal distress, increased shame, and more difficulty with interpersonal communication.…”
Section: Introductionmentioning
confidence: 99%